The ABCC2 c.-24C > T polymorphism increases the risk of resistance to antiepileptic drugs: A meta-analysis. (March 2017) - Qian, Long; Fang, Shu; Yan, Yuan-Liang; Zeng, Shuang-Shuang; Xu, Zhi-Jie; Gong, Zhi-Cheng
Highlights: ABCC2 variant c.-24C > T increases the risk of resistance to AEDs in epilepsy. No significant association of c.1249G > A, c.3972C > T variants with respond to AEDs. ABCC2 c.-24C > T polymorphism can act as a risk factor for resistance to AEDs. Abstract: Several studies examined a possible link between multidrug resistance-associated protein 2 (ABCC2) gene variants and the risk of resistance to antiepileptic drugs (AEDs) in epilepsy, but the results were contradictory. In this study, a meta-analysis was conducted to assess the relevance of ABCC2 common variants (c.-24C > T, c.1249G > A, c.3972C > T) with the response risk of AEDs. We searched Embase, PubMed, the Cochrane Library and CNKI databases for case-control studies published through May 2016 that evaluated the role of ABCC2 gene variants in pharmacoresistance to AEDs. Odds ratios (ORs) and their 95% confidence intervals (CIs) were calculated to assess the strength of associations between the ABCC2 c.-24C > T, c.1249G > A and c.3972C > T variants and the risk of resistance to AEDs using an allele frequency model, dominant model and recessive model. Subgroup analyses were performed by ethnicity and the definition of drug-resistance. A total of 13 published studies involving 4300 patients (2261 patients with drug-resistant epilepsy and 2039 controls with drug-responsive epilepsy) met the selection criteria. We observed that the variant c.-24C > T was associated with a significantly increased risk of AED resistance (TT + CT vs CC: OR = 1.24, 95%CI = 1.06–1.46, p = 0.009; TT vs CT + CC: OR = 1.90, 95%CI = 1.31–2.76, p = 0.0008; T vs C: OR = 1.27, 95%CI = 1.11–1.46, p = 0.0006). However, we identified no significant association of the ABCC2 c.1249G > A, c.3972C > T variants and haplotypes with the response to anticonvulsant drug in the overall population. In summary, these observations suggest that the ABCC2 c.-24C > T polymorphism is a likely risk factor for resistance to AEDs.